(3YeOI Phi GdCdbGHs - (3eMeO Hf jhSa Hf YeQ Hf TYjH GdMSfj GdSfhSj , CHh YHO Gddg, J (B895 (3g` s; (3GHf bWdhHZG , bGSe Hf bWdhHZG GdShOhfj GdLeGdj, Rjf GdOjf CHh GdYOd,J (B879 (3g` s
(3ChdgG (B:s
(3adeG cGf ef CYXe GdbhGYO GdJi cdafG HgG EbGeI GdUdGI s
(3BNQgG (B:s
(3hgh GdeQGab deQGO GdeDda QMeg Gddg JYGdi dfNJe HCf fbhd GdMeO ddg s
(3TQM CQLhRI HZjI GdWdGH ai GdBSWQdGHs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B111s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B255 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B74 s
Keywords: (3Gdadcs